PERFORMANCE ANALYSIS WEB BASED E-ALUMNI APPLICATION - Dodi Nofri Yoliadi (UIN Ar-Raniry, 2023)
Alumni are students who have completed the level of education with all the rules at a learning institution. So far, the alumni data collection at SMK Negeri 1 Batusangkar is still using the manual system. Therefore, a Web-Based Alumni Data Collection Application was built using the PHP programming language and database processing using Mysql and using the CodeIgniter framework. The purpose of this study is to analyze the performance and user satisfaction of this application. The method used in this study is a quantitative method using GTMetrix as software testing to analyze application performance and the PIECES evaluation model to analyze user satisfaction. Based on the measurement of application performance with GTMetrix, grade A is obtained, which means that the performance of the web application is good. Meanwhile, from the calculation of the level of user satisfaction, it is stated that of the six variables owned by the PIECES method, an average value of 4.26 is obtained which is in the range of 4.2 - 5.0 which means that the level of user satisfaction with this application is in the